Legal Protection for Patients in Telemedicine Services: A Legal Analysis of Nationally Applicable Regulations - Selvy Devita Anggeraini; Siti Marwiyah; Wahyu Prawesthi (Eduvest - Journal of Universal Studies, 2026)
The development of information and communication technology has driven the transformation of health services through telemedicine. Telemedicine provides easier access to remote health services, especially for people living in remote areas and those with limited access to health facilities. However, the implementation of telemedicine also raises various legal issues, particularly those related to patient protection, the confidentiality of medical data, informed consent, and the responsibilities of health workers. This research aims to analyze the legal regulation of telemedicine within Indonesia’s health law system, as well as the forms of legal protection provided to patients in telemedicine services. This research uses a normative juridical method with statutory and conceptual approaches. The results of the study show that telemedicine regulation in Indonesia has been established through Law Number 17 of 2023 concerning Health, Law Number 27 of 2022 concerning Personal Data Protection, Law Number 29 of 2004 concerning Medical Practice, Regulation of the Minister of Health Number 20 of 2019 concerning the Implementation of Telemedicine Services between Health Service Facilities, and Regulation of the Minister of Health Number 24 of 2022 concerning Medical Records. Legal protection for patients includes the protection of the right to information, the confidentiality of medical data, consent for medical procedures, and the legal responsibilities of health workers and telemedicine platform operators.